Experimental study of NBνN barrier structures based on MBE n-HgCdTe for MWIR and LWIR photodetectors - Voytsekhovskiy, Alexander V.; Dzyadukh, Stanislav M.; Gorn, Dmitriy Igorevich; Dvoretsky, Sergei A.; Mikhailov, Nikolay N.; Sidorov, Georgiy Yu; Yakushev, Maxim V. (Journal of communications technology and electronics)
The study is devoted to an experimental analysis of the electrical and photoelectric characteristics of barrier photosensitive structures in the NBνN configuration based on n-HgCdTe. Seven different types of photosensitive structures for MWIR and LWIR infrared ranges, grown by molecular beam epitaxy, have been studied. The current–voltage characteristics were measured both in the dark and under illumination. The parameters of the NBνN structure, which realizes the maximum values of the photocurrent and the minimum values of dark currents in the operating range of bias voltages V for elevated operating temperatures, are determined.